Effect of S. cerevisiae strain KA500 supplementation on feed performance, feed efficiency, and digestion ability in feedlot buffaloes - Ferreira, Maiara dos Santos; da Silva, Welligton Conceição; Cunha, Ancelmo Rodrigues; Costa, Ercvania Rodrigues; Cabral, Ícaro dos Santos; Dias, Salatiel Ribeiro; de Lima, Ronaldo Francisco (Frontiers in Veterinary Science, 2024)
Live yeasts have favorable characteristics for use in animal feed, and may become a beneficial tool to improve digestive efficiency in buffaloes (Bubalus bubalis). The productive performance, feed efficiency, and digestion ability of buffaloes fed diets supplemented with yeast (Saccharomyces cerevisiae strain KA500) were evaluated. Eighteen male Murrah buffaloes, with initial weight 250 ± 31 kg (mean ± standard deviation), and aged approximately 12 months, were randomly assigned to one of two treatments. The treatments included experimental feed containing 10 g of the live yeast capable of forming 2x10 10 colony forming units (CFU) and control (feed with no added yeast). The daily weight gain tended to be lower (p = 0.07) in buffaloes supplemented with yeast. There was a reduction in daily dry matter intake (DMI) and in % yield of live weight in buffaloes supplemented with yeast. There was no effect of live yeast supplementation on weight gain/kg dry matter intake, height at withers or rump, body condition score, total weight gain, carcass yield, plasma urea nitrogen concentrations, purine derivatives, and plasma glucose concentrations. The digestibility of dry matter (DM) and organic matter (OM) were lower (p < 0.05) with the supplementation of live yeast, although live yeast supplementation did not affect the digestibility of neutral detergent fiber (NDF) and non-NDF OM. The strain and dosage of live yeast used did not have a positive effect on buffalo performance and digestibility of dietary nutrients.